Flow driven robotic navigation of microengineered endovascular probes - Lucio Pancaldi (Nature Portfolio, 2020)
The navigation of catheters through blood vessels requires flexible guiding wires that are pushable and tractable at the same time. Pancaldi et al. rely on hydrodynamic forces and magnetic torque in order to access even rather small capillaries with an ultraflexible magnetomechanical probe.